Uveitis as an important ocular sign to help early diagnosis in Kawasaki disease - Han Seul Choi; Seul Bee Lee; Jung Hyun Kwon; Hae Soon Kim; Sejung Sohn; Young Mi Hong (Korean Pediatric Society, 2015)
PurposeIncomplete Kawasaki disease (KD) is frequently associated with delayed diagnosis and treatment. Delayed diagnosis leads to increasing risk of coronary artery aneurysm. Anterior uveitis is an important ocular sign of KD. The purpose of this study was to assess differences in laboratory findings, including echocardiographic measurements, clinical characteristics such as fever duration and treatment responses between KD patients with and those without uveitis.MethodsWe conducted a prospective study with 110 KD patients from January 2008 to June 2013. The study group (n=32, KD with uveitis) was compared with the control group (n=78, KD without uveitis). Laboratory data were obtained from each patient including complete blood count (CBC), erythrocyte sedimentation rate (ESR), platelet count, and level of alanine aminotransferase, aspartate aminotransferase, serum total protein, albumin, C-reactive protein (CRP), and N-terminal probrain natriuretic peptide (NT-pro BNP). Echocardiographic measurements and intravenous immunoglobulin responses were compared between the two groups.ResultsThe incidence of uveitis was 29.0%. Neutrophil counts and patient age were higher in the uveitis group than in the control group. ESR and CRP level were slightly increased in the uveitis group compared with the control group, but the difference between the two groups was not significant. No significant differences in coronary arterial complication and treatment responses were observed between the two groups.ConclusionUveitis is an important ocular sign in the diagnosis of incomplete KD. It is significantly associated with patient age and neutrophil count.